DESCRIPTION OF THE MANAGEMENT OF MEDICAL RECORD INPATIENT OF SYEKH YUSUF DISTRICT HOSPITAL GOWA 2019 - Zilfadhilah Arranury; Surahmawati Surahmawati,; Muhammad Rusmin; Tri Addya Karini; Dian Rezki Wijaya; Ranti Ekasari; Jihan Sulfitri (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
In the current era of global competition, it requires every hospital as a health service facility to be able to provide quality services in order to foster patient loyalty as service users. The medical record is one of the medical support services which is the basis for assessing the quality of medical services. Completeness of medical record files in RSUD Syekh Yusuf Kab. Gowa in a period of three years has fluctuated, namely 20% in 2017, 66% in 2018, and decreased in 2020 to 17%. This study aims to determine the description of medical record data management at RSUD Syekh Yusuf Kab. Gowa 2019.This study used a qualitative descriptive research method with the selection of informants using a purposive technique, and 6 informants were obtained, including 4 medical record officers, 1 head of the inpatient room, and 1 head of the medical records department.The results of the interview showed that the personnel in the medical records department were deemed insufficient, the flow and SOP were not implemented, the facilities and infrastructure were inadequate. In the implementation of medical records, there are still files that are filled in incompletely which results in delays in making reports.It is hoped that the hospital management will increase the number of personnel so that there is no double burden on officers, provide training for medical record officers, and pay attention to facilities and infrastructure to switch from a conventional system to an electronic-based system.